Proteomic/peptidomic profile and Escherichia coli growth inhibitory effect of in vitro digested soya protein - Carlotta Giromini; Simona Nonnis; David I. Givens; Julie A. Lovegrove; Raffaella Rebucci; Gabriella Tedeschi; Luciano Pinotti; Serena Reggi; Luciana Rossi; Antonella Baldi (Italian Journal of Animal Science, 2021)
Plant proteins contain bioactive peptides with functional properties and physiological activities. In the present work, the bioactive peptides produced during in vitro gastrointestinal digestion of soya protein isolate were investigated. Protein samples were subjected to simulated gastrointestinal digestion with a generation of permeate (<3 kDa) and retentate (>3 kDa) fractions. The permeate was analysed by nano-liquid chromatography electrospray ionisation tandem mass spectrometry (LC-nano ESI MS/MS) using a shotgun peptidomic approach, and the retentate was further digested with trypsin and analysed using a shotgun proteomic approach. Based on protein profile observed, the retentate was further tested for its potential antimicrobial activity by evaluating the inhibitory effect on E. coli growth. In the present study the peptidomic/proteomic characterisation of permeate and retentate fractions revealed the presence of bioactive peptides and proteins associated with antioxidant, ACE-inhibitory, anti-hypertensive and antimicrobial activities. The presence of potentially antimicrobial proteins in the retentate fraction is supported by a marked E. coli F18+ growth inhibitory activity of the same fraction. In particular, the growth inhibitory effect was significant from one until six hours of incubation with 0.65–2.6 mg/ml of in vitro digested soya. The obtained data confirmed that soya-based supplements may have potential beneficial effects after human consumption, and they may be re-cycled for animal nutrition in line with the circular economy concept.Highlights Soya-based supplements are relevant sources of bioactive molecules. Soya based supplements could be re-cycled for animal feeding considering the circular economy concept.